Marriage Anxiety Among Gen-Z Students: Examining Family Harassment Content Through the Lens of Islamic Family Law - A'la, Ahmad Zaim Muchlisi; CH, Mufidah; Hakeem, Akmal Rachman (Program Studi Hukum Keluarga Islam, 2026)
This study examines the influence of the digital trend “Marriage Is Scary” on pre-marital anxiety among Generation Z students and explores their coping mechanisms from the perspective of Islamic Family Law. The study is motivated by the widespread circulation of algorithm-driven digital content portraying domestic violence, infidelity, and dysfunctional family relationships, which increasingly shape young adults’ perceptions of marriage. Despite growing scholarly attention to digital culture and family issues, limited research has examined how digitally induced anxiety interacts with Islamic Family Law in shaping attitudes toward marriage. This research employs an empirical legal method with a qualitative approach through semi-structured interviews with 16 senior students at UIN Malang. The findings reveal two levels of anxiety based on Stuart’s classification: mild anxiety, which encourages self-reflection and marriage preparation, and moderate anxiety, characterized by fear, legal skepticism, and concerns about family stability arising from financial uncertainty, personal experiences, and digital cognitive dissonance. Students respond through adaptive strategies, including digital content filtering and cognitive reframing. This study contributes to the development of Islamic Family Law by demonstrating how digital environments reshape contemporary legal culture and underscores the importance of cyber-based pre-marital education and digital literacy to strengthen Muslim family resilience.